Measurement of degradation on under-utilized natural turf - Varga, Krisztina; Csízi, István (Acta Agraria Debreceniensis, 2020)
The role of turf serving animal husbandry is significantly declining with the decreasing number of grazing livestock in Hungary. Accordingly, the area of under-utilized or non-utilized turfs is increasing. At the University of Debrecen, Institutes for Agricultural Research and Educational Farm, Karcag Research Institute we studied four types of turf utilization in three repetitions on a salt meadow with Alopecurus pratensis. As a result of the performed examinations, we identified the composition of the flora structure on the investigated area and we measured carbon-dioxide circulation and soil moisture.